The Fiscal State-Dependent Effects of Capital Income Tax Cuts - Fotiou, Alexandra (IMF Working Papers; Working Paper ;, 2020)
Using the post-WWII data of U.S. federal corporate income tax changes, within a Smooth Transition VAR, this paper finds that the output effect of capital income tax cuts is government debt-dependent: it is less expansionary when debt is high than when it is low. To explore the mechanisms that can drive this fiscal state-dependent tax effect, the paper uses a DSGE model with regime-switching fiscal policy and finds that a capital income tax cut is stimulative to the extent that it is unlikely to result in a future fiscal adjustment. As government debt increases to a sufficiently high level, the probability of future fiscal adjustments starts rising, and the expansionary effects of a capital income tax cut can diminish substantially, whether the expected adjustments are through a policy reversal or a consumption tax increase. Also, a capital income tax cut need not always have large revenue feedback effects as suggested in the literature.